Demodulators for a zero-IF Bluetooth receiver. - Samadian, S. (IEEE Journal of solid state circuits)
This paper presents low-complexity detectors for a zero-IF Bluetooth receiver based on a simple phase-domain analog-to-digital converter. Measurements and simulations prove that the detectors' sensitivity lies close to an ideal coherent Gaussian frequency-shift keying (GFSK) detector.